Pengaruh Disiplin Kerja dan Beban Kerja Terhadap Kinerja Pegawai dalam Pelayanan Surat Menyurat pada Sub Bagian Umum dan Kepegawaian Dinas Ketenagakerjaan Kabupaten Bekasi - Aam Sumiati; Sungkono; Maman Mulya Karnama (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The aim of this research is to determine the effect of work discipline and workload on employee performance in the General and Personnel Subdivision of the Bekasi Regency Employment Service. The population and sample amounted to 60 employees. This research method uses a descriptive with a quantitative approach. The analysis used includes: classical assumption test, multiple correlation analysis, coefficient of determination test and significance test (t-test and F-test). The results of the work discipline research (X1) have a calculated t value of 9.071 which is greater than the t table with df = (60-2-1) of 1.996008 with a significance value of 0.001 < 0.05. Based on these values, it can be concluded that H0 is rejected, meaning that work discipline has a significant positive effect on employee performance partially. Meanwhile, workload (X2) has a calculated t value of 0.981 which is smaller than the t table with df = (60-2-1) of 1.996008 with a significance value of 0.331 > 0.05. Based on these values, it can be concluded that H0 is accepted, meaning that workload (X2) has a negative relationship and has an insignificant effect on employee performance (Y) partially.